Effects of different sedatives/analgesics on stress responses in patients undergoing craniotomy and bone flap decompression. Issue 12 (December 2021) - Guo, Qingduo; Ma, Meina; Yang, Qiuying; Yu, Hong; Wang, Xupeng; Wu, Chunling; Li, Rui
Objective: To explore the effects of sedation and analgesia with dexmedetomidine and other drugs on the stress response in patients with cerebral hemorrhage after craniotomy hematoma removal and bone flap decompression and insertion of an indwelling endotracheal catheter. Methods: A total of 180 patients with cerebral hemorrhage with consciousness disturbance who underwent emergency surgery were included in this study. They were divided into six groups treated with propofol, dexmedetomidine, lidocaine, sufentanil, dezocine, and remifentanil, respectively. Intravenous medication was given after recovery of spontaneous respiration, and stress responses were compared among the group. Results: Serum concentrations of norepinephrine, epinephrine, and cortisol and systolic blood pressure were significantly correlated with drug treatment. Serum norepinephrine concentrations differed significantly among the groups, except between the sufentanil and propofol groups. There were significant differences in serum epinephrine concentrations among all groups, and significant differences in serum cortisol concentrations among all groups, except the propofol, dexmedetomidine, and lidocaine groups. Conclusion: Dexmedetomidine can reduce the stress response in patients with intracerebral hemorrhage undergoing emergency craniotomy and bone flap decompression, and can reduce adverse events from an indwelling endotracheal catheter 3 hours post-operation.